Anti-AMPA receptor encephalitis with myasthenia gravis: a sinister combination associated with a high risk for underlying malignancy - Tahira Mohammad; Muhammad Ali Yousaf; Momina Qaisar; Farva Jalil; Tahir Aziz Ahmed (Journal of the Pakistan Medical Association)
A rare subtype of autoimmune encephalitis consists of antibodies targeting the alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor in the central nervous system. We describe the clinical presentation and autoimmune profile of the first case of alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor encephalitis with concurrent anti-acetylcholine receptor antibodies in Pakistan. The patient was a 58-year-old male who presented with the characteristic symptoms of limbic encephalitis with memory loss, irritability, agitation, and confusion. Antibodies against the alpha-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid receptor were detected in both serum and cerebrospinal fluid by indirect immunofluorescence. Computerised tomography of the chest showed an anterior mediastinal mass. The patient was treated with high dose Methylprednisolone and five sessions of plasma exchange. There was a short period of improvement; however, the patient now continues to exhibit irritability, aphasia, confusion, and memory loss.